Bioactive Nonthermal Biocompatible Plasma Enhances Migration on Human Gingival Fibroblasts (Adv. Healthcare Mater. 4/2023). Issue 4 (6th February 2023) - Han, Ihn; Song, In‐Seok; Choi, Seung Ah; Lee, Taebok; Yusupov, Maksudbek; Shaw, Priyanka; Bogaerts, Annemie; Choi, Eun Ha; Ryu, Jae Jun
Abstract : Oral Wound Healing In article 2200527 by Eun Ha Choi, Jae Jun Ryu, and co‐workers, nonthermal biocompatible plasma (NBP) stimulates human gingival fibroblast (HGF) cell migration through focal adhesion kinase (FAK) pathway. NBP inhibits colony formation and induces matrix metalloproteinase (MMP) expression, extracellular matrix (ECM) degradation, and subsequent cell migration. NBP plays a role in cell motility to regulate AKT and p21 signals in HGF cells, through actin modification of cytoskeleton.